Morpho-Physiological response of four native accessions of Phaseolus vulgaris L. subjected to water stress under greenhouse conditions in northeastern Peru - Santillan Huaman, Anlly (2024)
Phaseolus vulgaris L. is a legume of high nutraceutical value, widely cultivated and consumed. However, common bean production faces challenges such as water stress that severely affects its growth and yield. This study evaluated the morphological and physiological response of four native P. vulgaris accessions subjected to different irrigation treatments under greenhouse conditions. A completely randomized design with factorial arrangement was used, evaluating three irrigation frequencies (100%, 50%, 25%) in combination with four accessions (PER1003541, PER1003542, PER1003543, PER1003544). The results showed that with the 25% irrigation treatment, PER1003544 showed a 54.62% decrease in leaf area, while PER1003542 and PER1003543 experienced reductions of 56.56% and 59.24%, respectively. In addition, accession PER1003544 reported a smaller reduction in the number of flowers and pods, with decreases of 40.21% and 29.9%, in contrast to PER1003543, which showed decreases of 60.66% and 52.63%, respectively. Accessions PER1003541 and PER1003544 also recorded the lowest reductions in dry biomass, with 31.85%and 35.41%, respectively. Regarding yield, PER1003544 and PER1003541 experienced reductions of 59.01% and 69.79%, respectively, unlike PER1003543, which showed a 90% decrease. In relation to stomatal density, PER1003541 recorded a reduction of 28.28%, while PER1003544 had a decrease of 37.10%, and PER1003543 experienced a reduction of 47.05%; chlorophyll content showed a similar trend. Finally, PER1003544 maintained a relatively stable stomatal index, with a reduction of 29.01%, compared to PER1003543, which reduced by 60.99%. In conclusion, accession PER1003544 stands out as a promising variety for breeding programs focused on water stress tolerance, contributing to food security and agricultural sustainability in areas affected by limited water availability. However, PER1003541 would be a suitable additional option, offering farmers flexibility in their crop selection according to the specific conditions of their environment.